Communicating energy system modelling to the wider public: An analysis of German media coverage. (December 2017) - Scheer, Dirk
Abstract: This article researches communication of energy scenario modelling to the wider public by means of a media coverage analysis. Media coverage is interpreted as an indicator to what extent energy scenarios are a matter of public debate and deliberation. A total of 155 articles covering the time period 1992–2013 were considered for both structural and content media analysis. Communication on energy scenarios strikingly peaked in 2007 and 2010-12 covering 87% of the whole sample. As became clear from the empirical findings energy scenarios were present in media when pulled on stage by policy-makers themselves. As such, taking the 2007 and 2010 German energy policy events the framework setting were favorable to put energy scenario center stage in the media notwithstanding the tool itself seems not to be qualified for easy media communication. In case distinguished policy-makers and adequate media requirement settings reference energy scenarios they find their way into the media. Patterns of media representation embed the tool in public and/or politics controversy and play around the tensions between "generic factual knowledge claim" and "selective (in)consistency claim". To conclude, energy scenario seem to be vulnerable for strategic and tactical use in press reporting. However, in case high media coverage is given, chances arise for niches of transparent and objective science communication on modelling. Highlights: Communication of energy scenario modeling to the wider public. Energy scenarios strikingly peaked in 2007 and 2010-12. Energy scenarios highly present in media when pulled on stage by policy-makers. Patterns of media representation: "generic factual knowledge claim" vs. "selective (in) consistency claim". Energy scenario vulnerable for strategic and tactical use.